Factors affecting job performance of employees in Dungun municipal council - Mohd Milzam Nur Anuar
This research studies performance feedback, reward and training as the factors that influence job performance. Within this research, performance feedback, reward and training are the independent variables and the dependent variable is job performance. The research objectives and hypotheses were referred to guide the direction of this study. The data gathering throughout this research is quantitative in nature and the subjects of this research are employees of Dungun Municipal Council. The SPSS is the tool applied to analyze the primary data that collected using research questionnaire to determine the relationship between the independent variable and the dependent variable. Before the questionnaires were distributed to research subjects, the pre-test and pilot test were held to distinguish the validity and reliability of the items of the questionnaire. Then, data analysis procedures such as factor loading, reliability test, normality test, Pearson Correlation and Multiple Linear Regression were utilized to interpret the data gathered via the questionnaires forms to determine the relationship between the independent variables and dependent variable in this study. Besides, previous researches and articles regarding the similar topics were also gathered and scrutinized for the same reason. At the end of this study, the findings indicated that performance feedback and reward have positive and significant relationship with job performance while training has positive and insignificant relationship with the same dependent variable. Limitations and improvements were also discussed at the end of the study.